Acupuncture for emotional disorders in patients with inflammatory bowel disease: a systematic review protocol. Issue 9 (27th September 2022) - Zhou, Yuan-Fang; Zhang, Gui-Long; Sun, Ning; Wang, Zhong-Quan; Ye, Xiang-Yin; Xiong, Jian; Deng, Xiao-Dong; Lin, Xin; Zhang, Pei; Zheng, Hao; Zhang, Yong; Yang, Kun; et al.
Abstract : Introduction: Emotional disorders are often observed in inflammatory bowel disease (IBD). IBD with emotional disorders leads to poor quality of life. This systematic review aims to assess the effectiveness of acupuncture in patients with IBD with emotional disorders. Methods and analysis: Nine electronic databases, including Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, Allied and Complementary Medicine Database, Cumulative Index to Nursing & Allied Health Literature, China National Knowledge Infrastructure, Chinese Biomedical Literature Database, VIP Database and Wanfang Database, will be searched from inception to October 2021 without language restriction. The grey literature containing conference proceedings, as well as systematic reviews listed in the reference of definite publications, will also be retrieved. Randomised controlled trials either in English or Chinese reporting acupuncture therapy for IBD with emotional disorders will be included. The primary outcome is changes of emotional functioning outcomes. The Colitis Activity Index, Crohn's Disease Activity Index, C reactive protein and adverse events will be assessed as the secondary outcomes. More than two assessors will conduct the study retrieval and selection, as well as the data extraction and evaluation of the risk of bias. Data synthesis will be performed using a random-effects model based on the results of heterogeneity. Data analysis will be performed using RevMan software (V.5.4). Moreover, the dichotomous data will be presented as risk ratios, and the continuous data will be calculated using weighted mean difference or standard mean difference. Ethics and dissemination: This systematic review contains no individual patient data; thus, ethical approval is not required. Moreover, this review will be disseminated in a peer-reviewed journal or relevant conference. PROSPERO registration number: CRD42020176340.